The relationship of sleep quality and sleep hygiene with fatigability of resident physicians in a university hospital - Hengjeerajarusand, Natavuth; Inchai, Juthamas; Theerakittikul, Theerakorn (Biomedical Sciences and Clinical Medicine, 2019)
Objective To evaluate the association of sleep quality and sleep hygiene with fatigability of resident physicians. Methods A cross-sectional study was conducted using questionnaires to collect data from resident physicians from different departments in the Faculty of Medicine, Chiang Mai University, Thailand. Survey questions included demographic data and information regarding sleep and periods on duty. In addition, the questionnaire sets included the Pittsburg Sleep Quality Index (PSQI), the Sleep Hygiene Index (SHI), and the Stanford Sleepiness Scale (SSS). Results Of the 429 questionnaires distributed, 223 sets were returned (51.98%). The average hours of sleep per day when an overnight shift, time required to fall asleep, and the number of overnight shifts per month were 6.62 hours, 15.80 minutes, and 9.46 shifts, respectively. During an overnight duty shift, the average number of times a resident was awakened and the length of the actual sleep period were 3.67 times and 4.12 hours, respectively. The average scores of PSQI, SHI, and SSS while not on a shift and SSS while on a shift were 5.06±2.66, 30.96±8.27, 2.12±1.29, and 3.71±1.74, respectively. Significant relationships between sleep quality, sleep hygiene, and fatigability both before and after a shift were identified (p<0.05). Sleep quality and sleep hygiene had a significant effect on the fatigability of the resident physicians (SSS) after a period of being on duty. Each 1 point increase in PSQI resulted in a 0.25 point increase in SSS (95%CI 0.13-0.31, p<0.01). Similarly, a 1 point increase in SHI was accompanied by a 0.1 increase in SSS (95%CI 0.02-0.8, p<0.01). Hours of sleep per day when not working on a shift, the number of overnight shifts worked each month, and the number of hours worked per shift were found to have no relationship with sleep quality, sleep hygiene, or fatigability. Nevertheless, the number of incidents of being awakened and the average actual sleep time were significantly associated with sleep quality, sleep hygiene, and fatigability after shift work (p<0.05). Conclusion Sleep quality and sleep hygiene, both before and after an overnight duty shift, are significantly related with fatigability. Resident physicians who have both good sleep quality and good sleep hygiene have reduced fatigability.